Islamic worldview in comparative perspective - Abdul Razak, Mohd Abbas (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Humanity’s quest to understand the purpose of its existence and the meaning of life has led it in many directions in search of a philosophy that can offer a comprehensive explanation. Metaphorically, a worldview can be described as a lens through which humans perceive themselves and the world around them. In other words, a worldview is a philosophy of life that guides an individual in how to conduct life in this world. When discussing worldviews, only God knows the exact number followed by people across the globe. Broadly speaking, all worldviews can be classified into three main categories: scientific, philosophical, and religious.